A Comparative Study of Intrathecal Fentanyl And Dexmedetomidine For Prevention of Shivering After Spinal Anaesthesia In Caesarean Section - Bajaj , Radhika; Singam, Amol (International Journal of Psychosocial Rehabilitation, 2020)
Background: One of the common problematic complications following spinal anaesthesia is shivering which causes discomfort and discontent. It can enhance demand for oxygen and increase in production of CO2 about fourfold. Also, dexmedetomidine known to have sedative, analgesic, perioperative sympatholytic properties has shown effectiveness in suppressing postanesthesia shivering in patients. In comparison to intravenous route, intrathecal route focuses on the prevention of shivering rather than the control. Moreover, the administration of the drug combined with the spinal anaesthesia drug is more convenient and less time consuming and it promotes rapid onset of action. There is also less dose requirement with the intrathechal administration. Objectives: To compare the efficacy and safety of intrathecally administered fentanyl against dexmedetomidine in preventing post spinal shivering in patients posted for caesarean section under spinal anaesthesia. Methodology: All patients undergoing caesarean section will receive spinal anaesthesia in lateral or sitting position using 25G or 23 G Quincke needle in the L3-L4 intervertebral space via midline approach. After free flow of CSF, Group D will receive 10mg, 0.5% Bupivicaine (Heavy) combined with 5mcg dexmedetomidine in identical volume of 0.5ml, diluted with normal saline and Group F will receive 10mg (2ml), 0.5% Bupivicaine (hyperbaric) combined with 25ug (0.5ml) fentanyl Group F will receive 10mg (2ml), 0.5% Bupivicaine (hyperbaric) combined with 25ug (0.5ml) fentanyl. Results: We hypothesise lower incidence of shivering and prolong duration of post-operative analgesia in dexmedetomidine group compared to fentanyl group. Conclusion: We anticipate concluding Intrathecal dexmedetomidine has more efficacy and safety than intrathecally administered fentanyl in preventing post spinal shivering and need for post-operative rescue analgesia in patients posted for caesarean section under spinal anaesthesia. Keywords: Post spinal shivering, dexmedetomidine, fentanyl, spinal anaesthesia, caesarean section